2014
DOI: 10.1200/jco.2013.53.4115
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Brachytherapy on Local Recurrence Rates After Sublobar Resection: Results From ACOSOG Z4032 (Alliance), a Phase III Randomized Trial for High-Risk Operable Non–Small-Cell Lung Cancer

Abstract: Purpose A major concern with sublobar resection (SR) for non–small-cell lung cancer (NSCLC) is high local recurrence (LR). Adjuvant brachytherapy may reduce LR This multicenter randomized trial compares SR to SR with brachytherapy (SRB). Patients and Methods High-risk operable patients with NSCLC ≤ 3 cm were randomly assigned to SR or SRB. The primary end point was time to LR, where LR included recurrence at the staple line (local progression), in the primary tumor lobe away from the staple line, and in ipsila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 17 publications
4
51
0
2
Order By: Relevance
“…An initial presentation of the data at ASCO 2013 suggested that local recurrence and overall survival (OS) rates at 3-years were similar between arms. Fernando and colleagues 50 published the updated results with a median follow-up time of 4.38 years. Only 17 of 222 patients experienced local progression and there was no significant difference in the time to local recurrence or in the type of local recurrence with the addition of brachytherapy.…”
Section: Introductionmentioning
confidence: 99%
“…An initial presentation of the data at ASCO 2013 suggested that local recurrence and overall survival (OS) rates at 3-years were similar between arms. Fernando and colleagues 50 published the updated results with a median follow-up time of 4.38 years. Only 17 of 222 patients experienced local progression and there was no significant difference in the time to local recurrence or in the type of local recurrence with the addition of brachytherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The ACOSOG-Z4032 trial investigated the role of sublobar resection with brachytherapy versus sublobar resection alone [22]. Brachytherapy did not reduce the incidence of local recurrence after sublobar resection, underlying the importance of adequate surgical margins of sublobar resections.…”
mentioning
confidence: 99%
“…The primary endpoint of the study was local recurrence, and results were published in 2014 9 . There was no statistically significant difference in the time to local recurrence, the overall local recurrence rates, patterns of recurrence (local, regional or distant), or overall survival between sublobar resection with or without brachytherapy.…”
mentioning
confidence: 99%